The impact of pancreaticojejunostomy versus pancreaticogastrostomy reconstruction on pancreatic fistula after pancreaticoduodenectomy: meta‐analysis of randomized controlled trials. Issue 2 (February 2015) - Hallet, Julie; Zih, Francis S.W.; Deobald, Raymond G.; Scheer, Adena S.; Law, Calvin H.L.; Coburn, Natalie G.; Karanicolas, Paul J.
Abstract: Background: Pancreatic fistula (PF) remains a common source of morbidity following pancreaticoduodenectomy (PD). Despite numerous studies, the optimal method of pancreatic remnant reconstruction is controversial. This study examines the hypothesis that pancreaticogastrostomy (PG) is associated with a lower risk for PF after PD compared with pancreaticojejunostomy (PJ). Methods: Five electronic databases and the grey literature were searched for randomized controlled trials (RCTs) comparing PJ and PG after PD. Two reviewers independently selected studies, extracted data and assessed methodology. The primary outcome was the occurrence of PF of International Study Group on Pancreatic Fistula (ISGPF) Grade B or C. Results: Four RCTs including 676 patients were included. Pancreaticogastrostomy reduced the risk for PF [relative risk (RR) 0.41, 95% confidence interval (CI) 0.21–0.62] without any difference between high‐ and low‐risk patients. Absolute risk reduction for PF was 4% (95% CI 2.4–5.6) in low‐risk patients compared with 10% (95% CI 6.5–14.8) in high‐risk patients undergoing PG rather than PJ. The strength of evidence for PF outcome was moderate according to the GRADE classification. Conclusions: Reconstruction by PG decreases the rate of PF in comparison with PJ. Surgeons should consider reconstructing the pancreatic remnant following PD with PG, particularly in patients at high risk for PF.